Improvement of Student’s Learning Interest in Line Learning Using Powerpoint Media for Class VI - Wibawa, Dika Satriya (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research is to increase students' interest in learning using powerpoint media. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementing, observing, and reflecting stages. The subjects of this study were 23 students of grade VI SD Negeri 2 Sumurg in the 2020/2021 academic year. The data collection technique used a questionnaire. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of medi powerpoints can increase students' interest in learning in class VI SD Negeri 2 Sumurgede in the 2020/2021 school year as evidenced by the pre-cycle data of students who have very low interest by 17% reduced in cycle I to 0% and cycle II is also 0%. Then students who have low learning interest in the pre-cycle by 57% reduced in cycle I to 30% and in cycle II to 0%. Furthermore, students who have moderate interest in learning in the pre-cycle were 26% and increased to 57% and in the second cycle it became 61%. Meanwhile, students who have a high interest in learning in the pre-cycle by 0% increased in the first cycle to 13% and in the second cycle to 39%.